2017
DOI: 10.21010/ajtcam.v14i6.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Pine Needle Essential Oil From Different Habitats and Species of China by Gc-MS and Gc Method

Abstract: Background: Fresh pine needles, which evergreen, renewable and can be collected at any time, have abundant essential oil. The pine needle essential oil possess various biological activities, including antimicrobial, antioxidant, anti-inflammatory, cardioprotective properties etc., and can be widely used as medicine or medical raw materials, fragrances etc. So in order to make full use of pine needle plant resources, especially essential oil, the identification and quantification of essential oil were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The interest in the use of essential oils is due to their unique and excellent properties. Many studies have demonstrated antimicrobial activities, antioxidant activities, antiparasitic and insecticidal activities of essential oils [147][148][149][150][151]. Furthermore, essential oils have been investigated as control agents against growth of moulds and aflatoxin production [152][153][154][155].…”
Section: Plant Extracts Essential Oils and Compounds With Antifungal Activitymentioning
confidence: 99%
“…The interest in the use of essential oils is due to their unique and excellent properties. Many studies have demonstrated antimicrobial activities, antioxidant activities, antiparasitic and insecticidal activities of essential oils [147][148][149][150][151]. Furthermore, essential oils have been investigated as control agents against growth of moulds and aflatoxin production [152][153][154][155].…”
Section: Plant Extracts Essential Oils and Compounds With Antifungal Activitymentioning
confidence: 99%
“…It is usually obtained from medicinal and aromatic plants, herbs, and spices [28]. Several studies have demonstrated the antimicrobial, antiparasitic, antioxidant, and insecticidal activities of essential oils [29]. Moreover, essential oils have been investigated as controlling agents against molds growth and production of aflatoxins [24].…”
Section: Introductionmentioning
confidence: 99%
“…The results also show essential oils such as clove, garlic and rosemary oils and plant extracts such as garlic extract have antifungal activity. Several studies have shown that essential oils have antimicrobial, antiparasitic, antioxidant, and insecticidal activities (Yu et al, 2017). Furthermore, essential oils have been studied as inhibitors of mould growth and aflatoxins production (Zabka et al, 2009), which can be used to control crop diseases caused by soil-borne fungi.…”
Section: Figure 4: Antifungal Activity Of Natural Substances On Some ...mentioning
confidence: 99%